PRELIM - Suhaimy, Khairul Azman (Journal of Techno-Social, 2015)
PATRONAGE, SCIENTIFIC ADVISORY BOARD, EDITORIAL BOARD, ASSOCIATE EDITORS, EDITORIAL MANAGEMENT COMMITTEE, MESSAGE FROM EDITOR IN CHIEF, CONTENTS